Implementasi Fungsi Manajemen Dalam Pengelolaan Zakat Profesi Pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Asahan - Hilmiatu Sahla; Dian Wahyuni (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
The Professional Civil Servants (PNS) is the source of zakat income for National Amil Zakat Agency (BAZNAS) In Asahan Regency. This research was to analyze the implementation of management functions in the management of zakat for the profession of Civil Servants (PNS) in the National Amil Zakat (BAZNAS) of Asahan Regency and analyze the supporting and inhibiting factors in the management of zakat research. The method in this study was descriptive qualitative research. The data collection techniques made through interviews, observations and documentations, literiture study by international journal, BAZNAS data information, presentation, and conclusions.The result of study informed that one of the controlling function hadn’t been done effectively because of there weren’t the independent controlling council in BAZNAS stuctural ones as well as implementing the optimalization the collection of professional zakat with factors that support and provide solutions to existing constraints on the factors inhibiting professional zakat management activities.